Obtaining miRNA‐Target Interaction Information from miRWalk2.0. Issue 1 (20th April 2018) - Parveen, Alisha; Gretz, Norbert; Dweep, Harsh
Abstract: miRWalk2.0 (http://zmf.umm.uni‐heidelberg.de/mirwalk2 ) is a freely accessible, regularly updated comprehensive archive supplying the largest available collection of predicted and experimentally verified miRNA‐target interactions, with various novel and unique features to assist the scientific community. Approximately 949 million interactions between 11, 748 miRNAs, 308, 700 genes, and 68, 460 lncRNAs are documented in miRWalk2.0 with 5, 146, 217 different kinds of identifiers to offer a one‐stop site to collect an abundance of information. This article describes a schematic workflow on how to obtain miRNA‐target interactions from miRWalk2.0. © 2016 by John Wiley & Sons, Inc.